ANALISIS WACANA KRITIS BERITA PILGUB 2018 DALAM KORAN PONTIANAK POST - Priyanto, Bambang Eko; Martono, Martono; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract2018 is a political year for Kalimantan Barat (Kalbar) there are three pairs of Governor candidates. The focus of this research is that the researcher will analyze the 2018 governor's election news in the Pontianak Post Newspaper. The method used in the research is descriptive method and form qualitative research on the 2018 governor's headline text. Approach used AWK according to Teun A. Van Dijk which focused on three elements, namely aspects text, social cognition and context. The data source in this study is news 2018 Governor Election, while the data used is in the form of words, phrases and sentences relating to AWK on 2018 Governor Election news. Based on the results of the problem formulation in critical discourse analysis shows that in terms of news text there are some disadvantages such as incomplete 5w1h element in making news on 2019 Pilgub. Still available one news that only has two paragraphs. Researchers also found in terms of social cognition, news is not written directly by journalists Pontianak Post. Seeing in terms of social contests, the media that has made an appointment with the candidate pair will eliminate the side sensitivity in terms of criticizing.Keywords: Analysis of Critical Discourse, Text, Social Cognition, Social Context, Implementation of Learning Design.